Development of a Set of Chromosome Segment Substitution Lines in Pearl Millet [Pennisetum glaucum (L.) R. Br.]. Issue 5 (1st September 2014) - Kumari, B. Ramana; Kolesnikova‐Allen, Maria A.; Hash, C. Tom; Senthilvel, S.; Nepolean, T.; Kishor, P.B. Kavi; Riera‐Lizarazu, Oscar; Witcombe, J.R.; Srivastava, Rakesh K.
ABSTRACT: The detection of minor quantitative trait loci (QTL) with conventional mapping populations can be complicated by the overshadowing effect of major QTL as well as by interactions between QTL. To overcome these constraints, we developed a set of chromosome segment substitution lines (CSSLs) by introgression of overlapping chromosome segments from 863B into ICMB 841 background for use in QTL detection, fine mapping, and trait mechanism studies, especially for complex traits. Since each CSSL carries one or a few donor segments in the genetic background of the recurrent genotype, the QTL interaction is confined to genes present on small homozygous substituted segments. Advanced generation backcross progenies (1492), expected to provide coverage across the mapped length of each of the seven pearl millet linkage groups (LGs), were genotyped at 74 marker loci [(48 simple sequence repeats (SSRs), 21 single strand conformation polymorphism‐single nucleotide polymorphism (SSCP‐SNP), and 5 sequence tagged sites (STSs)] identifying 124 segment introgression homozygotes (13 for LG1, 9 for LG2, 10 for LG3, 41 for LG4, 23 for LG5, 11 for LG6, and 17 for LG7). These CSSLs consisted of 1–3 homozygous introgression segments substituted from 863B in the genetic background of the recurrent parent ICMB 841 and among them, 54 represent unique lines with the donor chromosome segment averaging 100.69 cM. These CSSLs developed here provide a nearly ideal set of genetic stocks for mapping and fine mapping the multitude of traits for which their parents differ.